Can Risk Stratification Based on Ultrasound Elastography of Background Liver Assist CEUS LI-RADS in the Diagnosis of HCC? - Li, Jiawu; Ling, Wenwu; Chen, Shuang; Yang, Lulu; Ma, Lin; Lu, Qiang; Luo, Yan (Frontiers in Oncology, 2021)
Objective To explore whether risk stratification based on ultrasound elastography of liver background assists contrast-enhanced ultrasound liver imaging reporting and data system (CEUS LI-RADS) in diagnosing HCC. Materials and Methods In total, 304 patients with focal liver lesions (FLLs) confirmed by pathology underwent CEUS and ultrasound elastography were included in this retrospective study. Patients with chronic hepatitis B (CHB, n=193) and non-CHB (n=111) were stratified by four liver stiffness measurement (LSM) thresholds. A LI-RADS category was assigned to FLLs using CEUS LI-RADS v2017. The diagnostic performance was assessed with the AUC, sensitivity, specificity, PPV, and NPV. Results The mean background liver stiffness of HCC patients with CHB, HCC patients without CHB and non-HCC patients without CHB were 9.72 kPa, 8.23 kPa and 4.97 kPa, respectively. The AUC, sensitivity, specificity and PPV of CEUS LI-RADS for HCC in CHB patients with LSM ≥ 5.8 kPa, ≥ 6.8 kPa, ≥ 9.1 kPa, and ≥ 10.3 kPa were high, with corresponding values of 0.745 to 0.880, 94.2% to 95.3%, 81.3% to 85.7%, and 98.1% to 98.8%, respectively. Higher AUC and specificity for HCC was observed in non-CHB patients with LSM ≥ 9.1 kPa and ≥ 10.3 kPa compared to non-CHB patients with LSM ≥ 5.8 kPa and ≥ 6.8 kPa, with corresponding values of0.964/1.000 vs 0.590/0.580, and 100%/100% vs 60%/70%, respectively. Conclusion CEUS LI-RADS has a good diagnostic performance in CHB patients regardless of the background liver stiffness. Furthermore, CEUS LI-RADS can be applied for non-CHB patients with a LSM ≥ 9.1 kPa.